Correlation of Significantly Decreased Serum Circulating Mesencephalic Astrocyte-Derived Neurotrophic Factor Level With an Increased Risk of Future Cardiovascular Disease in Adult Patients With Growth Hormone Deficiency - Ren, Ziyu; Wang, Yunting; Chen, Qing; Long, Jiangchuan; Zhang, Rui; Wu, Xun; Qian, Wenjie; Chen, Yue; Liu, Dongfang; Ren, Wei (Frontiers in Endocrinology, 2021)
Abstract Objective: Adult growth hormone deficiency (AGHD) is a rare chronic inflammatory disease caused by damage to the pituitary gland and is accompanied by disorders of multiple metabolic pathways. By examining the correlation between the serum mesencephalic astrocyte-derived neurotrophic factor (MANF) levels of AGHD patients and those of normal controls, we hope to elucidate the close relationship among MANF, lipid metabolism and insulin resistance in AGHD and discuss the potential therapeutic value of MANF. Methods: This study included 101 AGHD patients and 100 healthy subjects matched for sex, age, height, and weight. Anthropometric parameters and biochemical indicators such as body mass index, waist circumference, hip circumference, serum MANF level, blood lipids and insulin level were measured. The above patients were also divided into several subgroups for correlation analysis based on indicators such as insulin resistance and BMI. Results: The serum circulating MANF content of AGHD patients was significantly lower than that of the normal control group (5.235 (0.507-17.62) ng/ml (n=101) vs 10.30 (1.84-16.65) ng/ml (n=100); p<0.0001), and circulating MANF levels were linearly correlated with HOMA-IR in the AGHD population (R=0.481, P=0.0041). When MANF was at pathological concentrations (lower than the mean circulating MANF of normal controls), the lowest concentration tertile (OR=21.429 p<0.0001) had a significantly higher disease odds ratio, Framingham risk score and 10-year risk of atherosclerotic cardiovascular disease than the highest concentration tertile. Conclusions: MANF has a significant correlation with insulin resistance in the AGHD state. There is a strong correlation with abnormal glucose and lipid metabolism in the obese AGHD population. MANF is also a good assessment factor for the risk of cardiovascular disease in AGHD patients and has excellent therapeutic potential.